Conversations about Law - Burton, Howard (Ideas Roadshow Collections., 2021)
Conversations About Law is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring leading researchers with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection: 1. Nita Farahany, Robert O. Everett Distinguished Professor of Law and Professor of Philosophy at Duke University;2. Emilie Hafner-Burton, the John D. and Catherine T. MacArthur Professo.